Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the given system of equations:
[tex]\[ \begin{array}{l} 2.5 y + 3 x = 27 \\ 5 x - 2.5 y = 5 \end{array} \][/tex]
### Step 1: Adding the Two Equations
First, we add the two equations together:
[tex]\[ (2.5 y + 3 x) + (5 x - 2.5 y) = 27 + 5 \][/tex]
Let's combine like terms:
[tex]\[ 2.5 y - 2.5 y + 3 x + 5 x = 32 \][/tex]
[tex]\[ 0 + 8 x = 32 \][/tex]
[tex]\[ 8 x = 32 \][/tex]
So, the resulting equation from adding the two equations is:
[tex]\[ 8 x = 32 \][/tex]
### Step 2: Solving for [tex]\( x \)[/tex]
Now, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{32}{8} = 4 \][/tex]
### Step 3: Solving for [tex]\( y \)[/tex]
Next, substitute [tex]\( x = 4 \)[/tex] back into one of the original equations to find [tex]\( y \)[/tex]. Let's use the first equation:
[tex]\[ 2.5 y + 3(4) = 27 \][/tex]
[tex]\[ 2.5 y + 12 = 27 \][/tex]
Subtract 12 from both sides:
[tex]\[ 2.5 y = 27 - 12 \][/tex]
[tex]\[ 2.5 y = 15 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{15}{2.5} = 6 \][/tex]
### Final Solution
Thus, the resulting equation from adding the two equations is:
[tex]\[ 8 x = 32 \][/tex]
And the solution to the system of equations is:
[tex]\[ x = 4 \quad \text{and} \quad y = 6 \][/tex]
[tex]\[ \begin{array}{l} 2.5 y + 3 x = 27 \\ 5 x - 2.5 y = 5 \end{array} \][/tex]
### Step 1: Adding the Two Equations
First, we add the two equations together:
[tex]\[ (2.5 y + 3 x) + (5 x - 2.5 y) = 27 + 5 \][/tex]
Let's combine like terms:
[tex]\[ 2.5 y - 2.5 y + 3 x + 5 x = 32 \][/tex]
[tex]\[ 0 + 8 x = 32 \][/tex]
[tex]\[ 8 x = 32 \][/tex]
So, the resulting equation from adding the two equations is:
[tex]\[ 8 x = 32 \][/tex]
### Step 2: Solving for [tex]\( x \)[/tex]
Now, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{32}{8} = 4 \][/tex]
### Step 3: Solving for [tex]\( y \)[/tex]
Next, substitute [tex]\( x = 4 \)[/tex] back into one of the original equations to find [tex]\( y \)[/tex]. Let's use the first equation:
[tex]\[ 2.5 y + 3(4) = 27 \][/tex]
[tex]\[ 2.5 y + 12 = 27 \][/tex]
Subtract 12 from both sides:
[tex]\[ 2.5 y = 27 - 12 \][/tex]
[tex]\[ 2.5 y = 15 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{15}{2.5} = 6 \][/tex]
### Final Solution
Thus, the resulting equation from adding the two equations is:
[tex]\[ 8 x = 32 \][/tex]
And the solution to the system of equations is:
[tex]\[ x = 4 \quad \text{and} \quad y = 6 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.